Fish community response to in-channel woody debris in a channelized river system. Issue 1 (1st January 2019) - Archer, Michael W.; Pracheil, Brenda M.; Otto, Alexandrea E.; Pegg, Mark A.
Abstract: Additions of large wood (LW) have become a go-to technique for recovering altered river ecosystems. However, successful applications of this technique are generally limited to unchannelized rivers and headwater streams. Channelization of rivers, that is, engineering river channels to reduce recruitment and retention of in-channel structure, may, by definition, limit success of this restoration technique. Moreover, sufficient time has passed (a century or more) since initial channelization of many large rivers that portions of the fish community associated with LW may have become extirpated. Thus, the maxim that LW leads to a positive fish community response may not hold true. We examined fish community associations in habitats with and without LW in the channelized Missouri River to gain an understanding of the role of LW in large, channelized rivers. There were some differences between habitats with wood present compared to those without, but the differences were not evident once year, season and channel modifications intended to create aquatic habitat were taken into account. We assert that careful planning is necessary to ensure that additions of LW in channelized rivers are made to appropriate locations such that it will be retained in-channel for use as fish habitat and that LW-associated species are found in the system.